The Role Of Interactive Learning Media Based On Canva In Supporting Student Learning Outcomes - Meliyanti Meliyanti; Imma Rachayu; Yenni Fitria (Jurnal Komputer Indonesia, 2026)
This study aims to find out the role of Canva-based interactive learning media in supporting student learning outcomes and students' responses to its use in the Computer and Network Engineering subject for class X TKJT 2. The study uses a qualitative descriptive method with data collection techniques including observation, interviews, and questionnaires. The research subjects consist of class X TKJT 2 students and one teacher. The questionnaire was filled out by 26 students, while interviews were conducted with 10 students and 1 teacher. The results of the study show that Canva-based interactive learning media plays a role in supporting student learning outcomes by presenting material in a more interesting, interactive, and easy-to-understand way. Using Canva also helps increase students' attention, motivation, and activeness during the learning process. Students' responses to the use of Canva media reached a percentage of 89.43%, categorized as very good. These results indicate that students give Positive responses towards the material aspects, media appearance, as well as interactivity and use of technology. Based on the research results, it can be concluded that interactive learning media based on Canva plays a positive role in supporting students' learning outcomes and receives a very good response from students.